Learn typography using design tools - Mohd Daud, Sri Kusumawati; Hussain, Hanafizan; Osman, Md Najeb; Mustaffa, Fauzan (World Scientific and Engineering Academy and Society (WSEAS), 2007)
This paper will focus on the dynamics of group collaboration within a design project context and the application of design software tools. A typography design based project was used to create a collaborative learning environment with the aim of inculcating collaborative skills into the learners and increase their creative problem-solving and critical thinking skills. Therefore, the stud, were sought to measure the task skill which the focusing will be on the skills acquired in learning and the process skills which will be focus on the individual and group response during the completion of the task. The ability of students to produce good typography artwork according to the specific requirement was measured from the final artwork submitted.